Normal Macroscopic, Morphological, and Morphometric Parameters of the Esophagus of Whiterats - Temirov Orifjon Olimovich (Universitas Muhammadiyah Sidoarjo, 2022)
Histological methods of analysis of the morphofunctional status of the esophagus are widely used in the diagnosis and differential diagnosis of diseases of the gastrointestinal tract of various etiologies. However, their results do not always reflect the disruption of the entire organ structure. All this together increases the interest of researchers in the application of new methods of assessing esophageal pathology, which may be associated with microscopic evaluation of criteria for changes in esophageal pathomorphological structures, several anti-inflammatory agents, i.e. help detect changes in polypragmasic state. Therefore, macroscopic and microscopic studies of white esophageal rat esophagus were aimed at studying the normal data of esophageal tissue and comparing them with pathological processes, and 12 white non-white rat esophageal macroscopic and microscopic studies were performed.